GAMMA ANALYSIS : AN ANALYTICAL APPROACH TO DISCOVER ARCHITECTURAL GENOTYPES - Boutabba, Hynda; Mili, Mohamed; Boutabba, Samir-Djemoui; Farhi, Abdallah (My University, 2019)
This paper aims to highlight the basis of the space syntax approach, specifically the justified graph method or "gamma-analysis" in the identification of domestic architectural types according to their spatial organizations and their dwelling patterns. This identification is done through a concept borrowed from genetics and transmitted to architecture: The genotype and phenotype. Based on several examples, this article will explain the way in which the hidden socio-spatial structures of buildings will be highlighted. Originally used in Anglo-Saxon countries, this approach is currently used by a large number of researches focused on architectural spatiality especially domestic at the global level. The article will end with the critique of the method in terms of usefulness and significance of its results.
International Journal of Human Settlements Vol. 3 Nr. 3 2019
Keywords: spatial syntax; gamma analysis; genotype, phenotype; architectural spatiality; spatial organization